Dynamic Stability Improvement of Grid Connected DFIG Using Enhanced Field Oriented Control Technique for High Voltage Ride Through - Duggirala, V. N. Ananth; Gundavarapu, V. Nagesh Kumar (Journal of Renewable Energy, 2015)
Doubly fed induction generator (DFIG) is a better alternative to increased power demand. Modern grid regulations force DFIG to operate without losing synchronism during overvoltages called high voltage ride through (HVRT) during grid faults. Enhanced field oriented control technique (EFOC) was proposed in Rotor Side Control of DFIG converter to improve power flow transfer and to improve dynamic and transient stability. Further electromagnetic oscillations are damped, improved voltage mitigation and limit surge currents for sustained operation of DFIG during voltage swells. The proposed strategy has advantages such as improved reactive power control, better damping of electromagnetic torque oscillations, and improved continuity of voltage and current from stator and rotor to grid during disturbance. In EFOC technique, rotor flux reference changes its value from synchronous speed to zero during fault for injecting current at the rotor slip frequency. In this process, DC-Offset component of stator flux is controlled so that decomposition during overvoltage faults can be minimized. The offset decomposition of flux will be oscillatory in a conventional FOC, whereas in EFOC it is aimed to be quick damping. The system performance with overvoltage of 1.3 times, 1.62 times, and 2 times the rated voltage occurring is analyzed by using simulation studies.